1970
DOI: 10.1073/pnas.67.4.1878
|View full text |Cite
|
Sign up to set email alerts
|

Messenger and Heterogeneous Nuclear RNA in HeLa Cells: Differential Inhibition by Cordycepin

Abstract: Abstract. suppresses the labeling of messenger RNA in HeLa cells. The drug has no effect on either the labeling of nuclear heterogeneous RNA or on the transport of messenger RNA into the cytoplasm. The results suggest that messenger RNA and nuclear heterogeneous RNA are synthesized separately, and that the transcription of messenger RNA is inhibited by the drug.The nuclei of metazoan cells contain giant heterogeneous RNA. This species constitutes a major fraction of the RNA labeled during a pulse and turns ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1

Year Published

1973
1973
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(94 citation statements)
references
References 14 publications
6
87
1
Order By: Relevance
“…Because cordycepin interferes with polyadenylation, it was concluded that the probe must have been hybridized in the untreated cells. However, cordycepin has not been used in previous studies on mammalian cell nuclear RNA metabolism for more than 1-3 h (Siev et al, 1969;Penman et al, 1970;Darnell et al, 1971;Mendecki et al, 1972) because of severe toxicity effects. Moreover, it has been clearly established that cordycepin inhibits the production of cytoplasmic mRNA in HeLa cells within 25-40 min (Penman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because cordycepin interferes with polyadenylation, it was concluded that the probe must have been hybridized in the untreated cells. However, cordycepin has not been used in previous studies on mammalian cell nuclear RNA metabolism for more than 1-3 h (Siev et al, 1969;Penman et al, 1970;Darnell et al, 1971;Mendecki et al, 1972) because of severe toxicity effects. Moreover, it has been clearly established that cordycepin inhibits the production of cytoplasmic mRNA in HeLa cells within 25-40 min (Penman et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…However, cordycepin has not been used in previous studies on mammalian cell nuclear RNA metabolism for more than 1-3 h (Siev et al, 1969;Penman et al, 1970;Darnell et al, 1971;Mendecki et al, 1972) because of severe toxicity effects. Moreover, it has been clearly established that cordycepin inhibits the production of cytoplasmic mRNA in HeLa cells within 25-40 min (Penman et al, 1970). The mRNA population of HeLa cells consists of at least two kinetic components; 30 -40% has an average half-life of 2-7 h, and the rest has an average halflife of 24 h (Singer and Penman, 1973;Puckett and Darnell, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its structure, cordycepin could potentially interfere with any process requiring adenosine or ATP. In particular, cordycepin triphosphate was proposed to be a chain terminator for transcription, but it was reported early that total nuclear mRNA precursors are less affected than cytoplasmic mRNA (Penman et al 1970). In contrast, it has been demonstrated to be an efficient chain terminator for mRNA polyadenylation by poly(A) polymerases (Rose et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…8 Submerged cultivated C. militaris is found to secrete cordycepin into the environment. 20 Cordycepin is found to possess antitumor activity, 21 inhibition of nuclear RNA synthesis in nerve and glial cells, 22 and antiviral activity towards HIV-1 in vitro, 23 as well as antiprotozoal effect 24 and insecticidal activity against Plutella xylostella (L.). 25 Structure-growth inhibition relationships in intestinal organisms have been studied.…”
Section: Discussionmentioning
confidence: 99%